Handbook of Drug-Nutrient Interactions - Boullata, Joseph I.; Armenti, Vincent T. (Nutrition and Health, 2010)
Handbook of Drug-Nutrient Interactions, Second Edition is an essential new work that provides a scientific look behind many drug-nutrient interactions, examines their relevance, offers recommendations, and suggests research questions to be explored. In the five years since publication of the first edition of the Handbook of Drug-Nutrient Interactions new perspectives have emerged and new data have been generated on the subject matter. Providing both the scientific basis and clinical relevance with appropriate recommendations for many interactions, the topic of drug-nutrient interactions is significant for clinicians and researchers alike. For clinicians in particular, the book offers a guide for understanding, identifying or predicting, and ultimately preventing or managing drug-nutrient interactions to optimize patient care. Divided into six sections, all chapters have been revised or are new to this edition. Chapters balance the most technical information with practical discussions and include outlines that reflect the content; discussion questions that can guide the reader to the critical areas covered in each chapter, complete definitions of terms with the abbreviation fully defined and consistent use of terms between chapters. The editors have performed an outstanding service to clinical pharmacology and pharmaco-nutrition by bringing together a multi-disciplinary group of authors. Handbook of Drug-Nutrient Interactions, Second Edition is a comprehensive up-to-date text for the total management of patients on drug and/or nutrition therapy but also an insight into the recent developments in drug-nutrition interactions which will act as a reliable reference for clinicians and students for many years to come.